Time delay ODE/PDE models : applications in biomedical science and engineering - Schiesser, W. E. (Boca Raton : CRC Press, 2020)
"The intent of this book is to present a methodology for the formulation and computer implementation of mathematical models based on time delay ordinary differential equations (DODEs) and partial differential equations (DPDEs) in biomedical science and engineering (BMSE)"--
Introduction to Delay Ordinary Differential Equations -- Introduction to Delay Partial Differential Equations -- Hepatitis B Virus DPDE Model -- Tumor Induced Angiogenesis -- Metastatic Cancer Cell Invasion of Tissue -- Subcutaneous Injection of Insulin -- Hematopoietic Stem Cells -- Drug Eluting Stents.
OCLC-licensed vendor bibliographic record.
Keywords: Time delay systems -- Mathematical models; MEDICAL / Biotechnology; MATHEMATICS / Applied